Interferon-stimulated gene 15 facilitates BTV replication through interacting with the NS1 protein - Kang, Di; Zhang, Guorui; Zhang, Zhonghui; Tian, Zhancheng; Gao, Shandian; Liu, Guangyuan; Guan, Guiquan; Luo, Jianxun; Yin, Hong; Du, Junzheng (Frontiers in Microbiology, 2023)
Bluetongue virus (BTV) infection effectively activates the innate immune response, followed by the expression of interferon (IFN) and multiple interferon-stimulated genes (ISGs). Ovine ISG15 (oISG15) is one of the most induced ISGs, and often plays a role in inhibiting virus replication. In this study, we found that the transcription level of oISG15 was upregulated in a time-dependent and BTV multiplicity of infection-dependent manner. The overexpression of exogenous oISG15 enhances BTV replication, whereas the knockdown of endogenous oISG15 inhibits BTV replication. The viral protein in wild-type oISG15-overexpressed cells and ISGylation defective oISG15-overexpressed cells have no significant differences, which indicated that oISG15 promoted BTV replication in an ISGylation-independent manner. A co-immunoprecipitation assay showed that four viral BTV proteins—VP3, VP4, VP5, and NS1—interacted with oISG15. We also found that the VP4 and NS1 proteins associated with ubiquitin via co-immunoprecipitation, and that oISG15 overexpression improved the stability of both proteins. Further results showed that the degradation of NS1 was involved in Lysine 63-linked polyubiquitin. This suggested that oISG15 may interfere with NS1 degradation via the autophagy pathway. This study provides new insights on the interaction between BTV and ISG15, and enriches our understanding of the regulation and biological function of ISG15 with virus replication.